2020
DOI: 10.1186/s12935-020-01303-x
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA SNHG6 mainly functions as a competing endogenous RNA in human tumors

Abstract: Increased expression of the small nucleolar RNA host gene 6 (SNHG6) has been reported in different cancers, such as hepatocellular carcinoma, colorectal cancer, and lung cancer. The high expression level of SNHG6 is associated with tumor progression and poor prognosis. This paper provides an overview of recent studies on the oncogenic role and potential clinical utilities of SNHG6. Upregulated SNHG6 arrests tumor cell cycle and reduces apoptosis but promotes migration, invasion, metastasis, epithelial-mesenchy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 49 publications
1
15
0
Order By: Relevance
“…Recent studies have shown that lncRNAs often sponge many different types of miRNAs, acting as competing endogenous RNAs (ceRNAs) to achieve their function 22 - 24 . Because Linc01612 is mainly located in the cytoplasm, it is suspected that Linc01612 may function as a ceRNA to recover ATF3 expression by sponging miRNAs in HCC progression.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have shown that lncRNAs often sponge many different types of miRNAs, acting as competing endogenous RNAs (ceRNAs) to achieve their function 22 - 24 . Because Linc01612 is mainly located in the cytoplasm, it is suspected that Linc01612 may function as a ceRNA to recover ATF3 expression by sponging miRNAs in HCC progression.…”
Section: Resultsmentioning
confidence: 99%
“…To allow stratification of each patient according to their genomic characteristics, we successfully constructed a prognostic model using five FRLs, including SNHG6, LINC02298, AP000851.2, RPARP-AS1, and AL162274.1. Numerous studies have confirmed the prognostic value and clinical potential of SNHG6 in cancer, serving as a competitive endogenous RNA as one of the primary mechanisms underlying its role ( 84 ). According to Xu et al., SNHG6 expression is abnormally upregulated and regulated by SP1 in colorectal cancer, not only that SNHG6 promotes epithelial-mesenchymal transition and accelerates colorectal cancer growth and metastasis by competitively bound to miR-26a/b and miR-214 ( 85 ).…”
Section: Discussionmentioning
confidence: 99%
“…Knockdown of SNHG6 also inhibited BC cell migration, invasion and the EMT process. Besides BC, SNHG6 has been implicated as an important player in various tumors, such as hepatocellular carcinoma, gastric cancer, and bladder cancer [26][27][28]. Elevated SNHG6 level has been reported in those cancer cells and this elevation accelerates cancer cell proliferation and migration, indicating that SNHG6 has a conserved role as an oncogenic factor.…”
Section: Discussionmentioning
confidence: 99%